KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN GABUS (Channa striata) PADA BERBAGAI TINGKAT KETINGGIAN AIR MEDIA PEMELIHARAAN - Erick Extrada; Ferdinand Hukama Taqwa; Yulisman . (Universitas Sriwijaya, 2013)
ABSTRACT The purpose of this study was to determine survival rate and growth of snakehead juvenile (C. striata) at water elevation different levels of rearing media. The parameters observed during the study were survival, growth and water quality. This study used a complete randomized design with four treatments, namely maintaining the water level in rearing media of snakehead juvenile with the water level P1 (5 cm), P2 (10 cm), P3 (15 cm) and P4 (20 cm) with three replications. The results showed that the difference of culture media water levels significantly affect the survival rate, but not significantly effect on the growth of snakehead juvenile. The best survival rate obtained on media treatment P1 was to 96% and the lowest survival obtained at the media P3 was to 30,66%. Value for absolute length growth of snakehead juvenile highest in the treatmentÂ P2 with value 2,55 cm and the lowest in Â P4 treatment with a value of 2,14 cm. While the absolute weight growth of snakehead juvenile highest in treatment P3 with a value 0,81 g and the lowest weights in the treatment P4 with value 0,65 g. Keyword : Snakehead juvenile, water level, survival rate, growth, water quality